Electrospinning - Kurečič, Manja (Tekstilec, 2013)
Electrospinning is a method based on the use of electrostatic forces for producing continuous fi bres with the diameter from between ten nanometres to some micrometres. Such fi ne fi bres cannot be produced with conventional methods for the production of nonwovens. The nanofibres formed with electrospinning have an exceptionally large active surface area per mass unit (fibre surface at diameter of 100 nm equals 40 m2/g) and the spinning process itself enables a planned formation of the web structure (e.g. planned size of pores in the web by adjusting the nanofi bre diameter and fibre thickness). Nanofibres can be electrospun from synthetic or natural polymers and their blends, from polymers with various nanoparticles (metal, ceramic etc), active substances etc. We can fabricate individual fibres, as well as webs with a random or planned fibre arrangement. Fibres with a complex structure, e.g. core shell or hollow fibres, can be produced with a special electrospinning method. Regarding the advantages demonstrated by the nanofibres fabricated with electrospinning, this procedure has become an important part of research in seve ral fi elds of use of technical textiles, e.g. shielding materials, air and oil filters in the car industry, agrotextiles and most of all medical textiles. The method can also be used in the production of batteries and photovoltaic cells. Apart from the apparatus designed for the research purpose in laboratories, pilot devices and the devices designed for the use in the industry can be found on the market. The paper comprises the introduction of the preparation procedure of nanofibres on an electrospinning apparatus, the morphological characteristics of fibres and the characteristics of electrospun webs in dependence of the conditions when forming fibres.
Keywords: 3D-structure; electrospinning; elektropredenje; nanofibres; nanotechnology; nanotehnologija; nanovlakna